2.4 GHz Microstrip Band Pass Filter - Othman, Abdul Rani; Wasli, Chairulsyah (2006)
This report insight the design, fabrication and testing of 2.4 GHz Bandpass Filter developed by using Microstrip Technology. The results acquired through R & D process have been simulated, analyzed and verified by using parallel-coupled lines filter topology, which were later, enhanced by various value-aided software tools such as MATLAB (V 7.0), CorelDraw 12, Microwave Office (2004). For the optimal result, three samples were fabricated with the help of Microwave Office tools. The comparative filter response analyses were carried out with the help of vector network analyzer, which gives the best choice for further analysis and development. Comparative analyses were carried out for the optimization of both experimental and analytical data acquired through the design, simulation, and fabrication and testing process of the bandpass filter. Subsequent results demonstrate, through verification process, that the experimental results (measured) gives more or less same performance compare analytical one (calculated).